2019
DOI: 10.3892/ol.2019.10264
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diagnostic values between CA125 combined with CA199 and ultrasound combined with CT in ovarian cancer

Abstract: Application values of CA125 combined with CA199 and ultrasound combined with computed tomography (CT) in the clinical diagnosis of ovarian cancer were compared. A retrospective analysis was performed on 168 ovarian cancer patients admitted to the Department of Gynecology in Jining No.1 People's Hospital from July 2013 to March 2016. Of the patients 107 with malignant tumors were in the malignant group, and 61 patients with benign tumors were in the benign group. Another 98 healthy controls in the same period w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
0
16
1
Order By: Relevance
“…However, due to the overlapping features of SMOTs and SBOTs, a definitive diagnosis should not be made based on imaging alone or single tumor biomarkers. Several studies depending on imaging combined with tumor markers and multi-biomarker methods have been applied to increase the sensitivity and specificity of diagnosing early-stage ovarian cancer [ 14 , 19 , 30 ]. Guo et al [ 18 ] reported that the combination of CA125, CA19-9, and CEA markers was a promising method for detecting epithelial ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the overlapping features of SMOTs and SBOTs, a definitive diagnosis should not be made based on imaging alone or single tumor biomarkers. Several studies depending on imaging combined with tumor markers and multi-biomarker methods have been applied to increase the sensitivity and specificity of diagnosing early-stage ovarian cancer [ 14 , 19 , 30 ]. Guo et al [ 18 ] reported that the combination of CA125, CA19-9, and CEA markers was a promising method for detecting epithelial ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the same scenario, the diagnostic rates increase with contrast administration, up to 81% (CI, 77ā€“84%) sensitivity and 98% (CI, 97ā€“99%) specificity [ 24 ]. Other reports show different sensitivity rates, such as the study conducted by Guo [ 25 ], which showed that CT had a sensitivity of 83.18% and a specificity of 85.25% in 168 patients. Altogether, our results, although showing medium-high diagnostic power for detecting malignant tumors, cannot outperform the classic CT evaluation of these lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The early diagnosis of OC is of great importance to increase the survival of the patients. [19][20][21] It is still unclear whether ADAM9 can serve as potential diagnostic biomarker for OC. In this study, we further explored the potential diagnostic value of ADAM9 using fresh OC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The early diagnosis of OC is of great importance to increase the survival of the patients . It is still unclear whether ADAM9 can serve as potential diagnostic biomarker for OC.…”
Section: Discussionmentioning
confidence: 99%